3D-Printed Hydrogels in Orthopedics: Developments, Limitations, and Perspectives - Liu, Zhen; Xin, Weiwei; Ji, Jindou; Xu, Jialian; Zheng, Liangjun; Qu, Xinhua; Yue, Bing (Frontiers in Bioengineering and Biotechnology, 2022)
Three-dimensional (3D) printing has been used in medical research and practice for several years. There are various aspects thatVarious aspects can affect the finished product of 3D printing, and it has been observed that the impact of the raw materials used for 3D printing is unique. Currently, hydrogels, including various natural and synthetic materials, are the most biologically and physically advantageous biological raw materials, and their use in orthopedics has increased considerably in recent years. 3D-printed hydrogels can be used in the construction of extracellular matrix during 3D printing processes. In addition to providing sufficient space structure for osteogenesis and chondrogenesis, hydrogels have shown positive effects on osteogenic and chondrogenic signaling pathways, promoting tissue repair in variousmany dimensions. 3D -printed hydrogels are currently making a splashattracting extensive attention infor the treatment of bone and joint injuries owingdue to the above-mentioned significant advantages. What’s moreFurthermore, hydrogels have been recently used in infection prevention because of their antiseptic impact induring the perioperative period. However, there are a few shortcomings associated with hydrogels including difficulty in getting rid of the constraints of the frame, poor mechanical strength, and burst release of loadings. These drawbacks could be overcome by combining 3D printing technology and novel hydrogel material through a multi-disciplinary approach. In this review, we provide a brief description and summary of the unique advantages of 3D printing technology in the field of orthopedics. In addition, some 3D printable hydrogels possessing prominent features, along with the key scope for their applications in bone joint repair, reconstruction, and antibacterial performance, are discussed to highlight the considerable prospects of hydrogels in the field of orthopedics.